2009
DOI: 10.1016/j.micres.2006.11.016
|View full text |Cite
|
Sign up to set email alerts
|

A protein linkage map of the ESAT-6 secretion system 1 (ESX-1) of Mycobacterium tuberculosis

Abstract: Tuberculosis is a chronic infectious disease caused by bacteria of the Mycobacterium tuberculosis complex. One of the major contributors to virulence and intercellular spread of M. tuberculosis is the ESAT-6 secretion system 1 (ESX-1) that has been lost by the live vaccines Mycobacterium bovis BCG (Bacille Calmette Guérin) and Mycobacterium microti as a result of independent deletions. ESX-1 consists of at least 10 genes (Rv3868-Rv3877) encoding the T-cell antigens ESAT-6 and CFP-10 as well as AAA-ATPases, cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 23 publications
7
41
0
2
Order By: Relevance
“…24 The inactivation of PPE68 leads to an enhancement of the secretion of ESAT-6, suggesting that PPE68 is likely to have a role and participates in the control of secretion by the type VII secretion apparatus. 17 Similar observation has been made regarding the role of PPE68 protein by other groups. 26 This raises an important question: why the inactivation of PPE68, associated with increased secretion of ESAT-6, decreases the necrotic cell death as observed in our assays.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…24 The inactivation of PPE68 leads to an enhancement of the secretion of ESAT-6, suggesting that PPE68 is likely to have a role and participates in the control of secretion by the type VII secretion apparatus. 17 Similar observation has been made regarding the role of PPE68 protein by other groups. 26 This raises an important question: why the inactivation of PPE68, associated with increased secretion of ESAT-6, decreases the necrotic cell death as observed in our assays.…”
Section: Discussionsupporting
confidence: 81%
“…23 Recent studies have demonstrated that PPE68 is a significant immunogenic component of RD1 and most likely plays an important role in Mtb pathogenicity. 24 The profile of PPE68 interacting Mtb proteins Studies provide evidence that PPE68 interacts with multiple components of the ESX-1 machinery 17,25 and results further indicate that disruption of PPE68 is associated with increased secretion of ESAT-6 effector protein, suggesting the possible role of PPE68 as a gating protein during the type VII-dependent (2), Rv1093/glyA1 (3), Rv1388/mihF (4), Rv1837c/glcB (5), Rv2220/glnA1 (6) and Rv2626c (7) were confirmed using a yeast 2-hybrid system. To test the specificity of PPE68 interaction to target Mtb proteins, the yeast reporter strain containing the bait pGBKT7:PPE4 and pGBKT7:PPE27 constructs were screened against the selected Mtb gene constructs in pGADT7 vector; The yeast zygotes that grew on quadruple dropout medium SD/-Ade/-His/-Leu/-Trp supplemented with X-a-Gal and Aureobasidin A (QDO/X/A) and turned blue in color were considered positive.…”
Section: Necrosis Deficient Mutants Are Associated With Delayed Activmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum CFP-10 was detectable at lower concentrations than ESAT-6, perhaps owing to variable expression levels of ESAT-6 and CFP-10 in different strains of Mtb (40,41). However, host β2 microglobulin also has been reported to bind ESAT-6 to mask a tryptic cleavage site (amino acids 90-95) required for the 1,900.95 m/z ESAT-6 peptide (16,42), and thus may inhibit ESAT-6 cleavage to decrease the apparent serum ESAT-6 levels in our assay.…”
Section: Discussionmentioning
confidence: 99%
“…EccA is an ATPase that may be involved in dissociating the EspG-PPE interaction because (i) EccA proteins are only encoded in ESX gene clusters that also encode PE and PPE proteins, (ii) EccA mutants accumulate PPE-bound EspG (22), and (iii) EccA interacts with both PPE protein (35) and EspG (SI Appendix, Fig. S12) in yeast two-hybrid assays.…”
Section: Espg Encoded In the Esx-5 Gene Cluster Of Mtb Interacts Exclmentioning
confidence: 99%